Educator's Perspective on the Implementation of an Independent Curriculum in Arabic Learning at MTs Negeri Malinau, North Kalimantan: Perspektif Pendidik terhadap Implementasi Kurikulum Merdeka dalam Pembelajaran Bahasa Arab di MTs Negeri Malinau, Kalimantan Utara - Anis Fitriah; Fitri Zakiyah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
Implementing the Merdeka Independent Curriculum has evoked diverse reactions, particularly among teachers, giving rise to issues such as a lack of training or orientation, hasty adjustments, and various controversies, particularly affecting schools far from the central government. Consequently, these challenges have resulted in schools needing help seamlessly implementing the Curriculum. The controversies have triggered varied perceptions concerning the Independent Curriculum's implementation. This research aims to examine the implementation of the Independent Curriculum and elucidate teachers' perspectives on the implementation of the Independent Curriculum in Arabic language learning at MTs Negeri Malinau. The researcher used a qualitative method based on the Miles and Huberman framework to collect data through observations and interviews at MTs Negeri Malinau. The researcher treated educators and the Independent Curriculum's implementation as subjects and objects. The results show that instructors, including the curriculum coordinator and school principal, have generally positive opinions about applying the Independent Curriculum to Arabic language instruction. They state that the Curriculum is considered adequate and fits the needs of the students. Still, problems remain, chiefly related to inadequate infrastructure. Notwithstanding these challenges, MTs Negeri Malinau uses a variety of tactics to carry out the Independent Curriculum and is optimistic about its successful implementation. Keywords: Arabic Language, Independent Curriculum, Perception   Abstrak Penerapan Kurikulum Merdeka menimbulkan beragam tanggapan, terutama dari kalangan guru. Timbulnya persoalan bermula dari kurangnya pelatihan atau sosialisasi, waktu perubahan yang terkesan tergesa-gesa dan munculnya berbagai polemik terutama bagi sekolah-sekolah yang jauh dari pemerintahan pusat sehingga membuat sekolah harus terbata-bata dalam menerapkan kurikulum ini. Banyaknya permasalahan yang muncul memicu beragam persepsi terkait penerapan kurikulum merdeka. Penelitian ini bertujuan untuk mendeskripsikan persepsi guru terhadap implementasi Kurikulum Merdeka dalam pembelajaran bahasa Arab di MTs Negeri Malinau serta mengetahui bentuk penerapannya. Penelitian ini menggunakan metode kualitatif menggunakan pendekatan Miles and Huberman. Peneliti menggunakan observasi dan wawancara untuk mengumpulkan data yang bersumber dari guru-guru MTs Negeri Malinau dan penerapan kurikulim merdeka sebagai subjek dan objek penelitian. Hasil penelitian ini menunjukkan bahwa persepsi para guru, termasuk kepala sekolah dan waka kurikulum, terhadap penerapan KurikulumMerdeka dalam pembelajaran bahasa Arab, adalah positif. Mereka menyatakan bahwa kurikulum ini dianggap sudah cukup baik dan relevan dengan kebutuhan peserta didik. Meskipun demikian, terdapat kendala dalam penerapannya, terutama terkait dengan fasilitas yang kurang mencukupi. Bentuk penerapan Kurikulum Merdeka di MTs Negeri Malinau sangat beragam. Meski terdapat hambatan fasilitas, sekolah tetap optimis dapat melaksanakan Kurikulum Merdeka dengan baik. Kata Kunci: Bahasa Arab, Kurikulum Merdeka, Persepsi